Preparticipation predictors for championship injury and illness: cohort study at the Beijing 2015 International Association of Athletics Federations World Championships. Issue 4 (8th November 2016) - Timpka, Toomas; Jacobsson, Jenny; Bargoria, Victor; Périard, Julien D; Racinais, Sébastien; Ronsen, Ola; Halje, Karin; Andersson, Christer; Dahlström, Örjan; Spreco, Armin; Edouard, Pascal; Alonso, Juan-Manuel
Abstract : Objectives: To determine preparticipation predictors of injury and illness at a major Athletics championship. Methods: A cohort study design was used. Before the 2015 International Association of Athletics Federations World Championships in Athletics, all 207 registered national teams were approached about partaking in a study of preparticipation health; 50 teams accepted. The athletes (n=957) in the participating teams were invited to complete a preparticipation health questionnaire (PHQ). New injuries and illnesses that occurred at the championships were prospectively recorded. Logistic regression analyses were performed with simple and multiple models using any in-championship injury and in-championship illness as outcomes. Results: The PHQ was completed by 307 (32.1%) of the invited athletes; 116 athletes (38.3%) reported an injury symptom during the month before the championships, while 40 athletes (13%) reported an illness symptom. 20 (6.5%) of the participating athletes sustained a health problem during the championships. Endurance athletes were almost 10-fold more likely to sustain an in-championship illness than speed/power athletes (OR, 9.88; 95% CI 1.20 to 81.31; p=0.033). Participants reporting a preparticipation gradual-onset injury symptom were three times more likely (OR, 3.09; 95% CI 1.08 to 8.79; p=0.035) and those reporting an illness symptom causing anxiety were fivefold more likely (OR, 5.56; 95% CI 1.34 to 23.15; p=0.018) to sustain an in-championship injury. Summary and conclusions: Analyses of preparticipation predictors of injury and illness at a major Athletics championship suggest that endurance athletes require particular clinical attention. Preparticipation symptoms causing anxiety are interesting predictors for in-championship health problems.